2012
DOI: 10.1158/0008-5472.can-12-0429
|View full text |Cite
|
Sign up to set email alerts
|

AMPK Promotes p53 Acetylation via Phosphorylation and Inactivation of SIRT1 in Liver Cancer Cells

Abstract: AMP-activated protein kinase (AMPK), a biologic sensor for cellular energy status, has been shown to act upstream and downstream of known tumor suppressors. However, whether AMPK itself plays a tumor suppressor role in cancer remains unclear. Here, we found that the a2 catalytic subunit isoform of AMPK is significantly downregulated in hepatocellular carcinoma (HCC). Clinicopathologic analysis revealed that underexpression of AMPK-a2 was statistically associated with an undifferentiated cellular phenotype and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
179
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(186 citation statements)
references
References 32 publications
5
179
2
Order By: Relevance
“…In addition, the deacetylase activity of Sirt1 was observed to decrease when Sirt1 mutants were transcribed and translated using the site-directed mutagenesis method in a model of carcinogenesis, which increased the sensitivity of cells to DNA damage and the oxidative stress response (26). Further studies demonstrated that the addition of a specific inhibitor of Sirt1, 5' adenosine monophosphate-activated protein kinase, into human hepatoma HepG2 and PLC/PRF/5 cells led to significant reductions in the activity and function of Sirt1, resulting in increased acetylation and transcriptional activity of the p53 protein (27,28). In addition, previous studies noted that Sirt1 expression in primary colorectal carcinoma was significantly increased, suggesting that Sirt1 is key in the occurrence and development of intestinal tumors (29).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the deacetylase activity of Sirt1 was observed to decrease when Sirt1 mutants were transcribed and translated using the site-directed mutagenesis method in a model of carcinogenesis, which increased the sensitivity of cells to DNA damage and the oxidative stress response (26). Further studies demonstrated that the addition of a specific inhibitor of Sirt1, 5' adenosine monophosphate-activated protein kinase, into human hepatoma HepG2 and PLC/PRF/5 cells led to significant reductions in the activity and function of Sirt1, resulting in increased acetylation and transcriptional activity of the p53 protein (27,28). In addition, previous studies noted that Sirt1 expression in primary colorectal carcinoma was significantly increased, suggesting that Sirt1 is key in the occurrence and development of intestinal tumors (29).…”
Section: Discussionmentioning
confidence: 99%
“…AMPK is known to function as an intracellular energy sensor, being activated in response to an increased AMP⁄ATP ratio, a condition of energetic stress, to promote the catabolic pathway, thereby inhibiting cell proliferation (18,19). Growing evidence suggests that AMPK is dysregulated in most cancer tissues, including HCC, when compared to normal tissues (26)(27)(28), and several studies have shown that AMPK activators exhibit inhibitory effects on HCC growth (21,26,27,(29)(30)(31)36). Scientific interest continues to grow in the search for molecular pathways and novel compounds that target AMPK signaling as new potential therapeutic options for HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Under metabolic stress conditions, where decreases in intracellular ATP and increases in AMP levels are common, AMPK is activated by phosphorylation of a critical amino acid residue (Thr172) to function as a major metabolic switch that maintains energy homeostasis (18,19). Once activated, AMPK suppresses cell proliferation in tumor as well as non-tumor cells, through regulation of the cell cycle, apoptosis, autophagy, and inhibition of protein synthesis (20)(21)(22)(23)(24)(25). Current evidence supports the alteration of AMPK levels in various cancers, implicating AMPK as a potential target for prevention and/or treatment of cancer, specifically HCC (26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%
“…This involves the inhibition of energy‐consuming processes such as fatty acid and protein biosynthesis, while increasing catabolism by promoting autophagy and fatty acid oxidation (Carling et al ., 2012; Faubert et al ., 2015; Mihaylova and Shaw, 2011). In addition to direct regulation of key metabolic checkpoints, AMPK may also inhibit tumorigenesis through upregulation of transcription factors such as the tumor suppressor p53, which is mutated in approximately 80% of all cancers (He et al ., 2014; Jones et al ., 2005; Lee et al ., 2012). Mutation or genetic deficiency of p53 may also act to suppress AMPK activity (Zhou et al ., 2014), suggesting that the activities of p53 and AMPK may be intimately linked to match energy availability with cell proliferation (Adamovich et al ., 2014).…”
Section: Introductionmentioning
confidence: 99%